Asthma and its comorbidities in middle-aged and older adults; the Rotterdam Study. (June 2018) - de Roos, Emmely W.; Lahousse, Lies; Verhamme, Katia M.C.; Braunstahl, Gert-Jan; Ikram, M. Arfan; in 't Veen, Johannes C.C.M.; Stricker, Bruno H.Ch.; Brusselle, Guy G.O.
Abstract: Background: Little is known on the prevalence and characteristics of asthma in middle-aged and older adults, since previous studies mainly focused on children and young adults. Therefore, the aim was to investigate the prevalence of physician-diagnosed asthma and its comorbidities, in a population-based cohort of adults 45 years of age and over. Methods: We identified participants with physician-diagnosed asthma in the Rotterdam Study; a prospective population-based cohort in the Netherlands. Pulmonary function measurements and comorbidities of the asthma cases were assessed at baseline and compared to those of the general population. Results: Out of 14, 621 participants (mean age 65.5 years; 59% women), 524 subjects (31.5%males) had physician-diagnosed asthma at study entry, implicating an asthma prevalence of 3.6% [95% Confidence Interval (CI) 3.3%–3.9%] (2.8% in males and 4.2% in females). Asthmatic subjects had a significantly higher prevalence of obesity and depressive symptoms (Odds Ratio [OR]: 2, 02 [95% CI 1, 66-2, 47] and [OR]: 2, 01 [95% CI 1, 52-2, 66] respectively). Longer duration of asthma and current smoking were associated with lower lung function in asthmatic subjects. Conclusion: Four percent of middle-aged and older adults have physician-diagnosed asthma. These adult asthmatics suffer more frequently from obesity and depression than subjects without obstructive lung disease. Highlights: At least 3, 6% of adults over 45 years is diagnosed with asthma. Asthma in older adults is strongly associated with obesity and depression. Asthmatics have significantly lower lungfunction compared to the general population.